The Sustainability of Agro-Food and Natural Resource Systems in the Mediterranean Basin 2015
DOI: 10.1007/978-3-319-16357-4_23
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical Techniques for Plant, Soil, and Root Research Related to Sustainability

Abstract: The sustainable management of human activities, from production to waste disposal and the cycling of finite resources, is one of the great challenges of research for the coming decades, stemming from societal needs and the growing awareness of environmental mechanisms.Research on geophysical methods provides an interdisciplinary approach to such challenges by addressing the need for techniques to assist in designing and monitoring strategies for sustainability in agriculture and other environment-related scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
0
4
0
2
Order By: Relevance
“…In this respect, there is a growing demand for near-surface observing technologies (e.g. geophysical methods) to study agriculturally significant phenomena in the soil (Bitella et al, 2015). Recent studies (Cassiani et al, 2015;Consoli et al, 2017;Satriani et al, 2015) demonstrated that these techniques can improve irrigation operations by providing information regarding the optimal amounts and timing of irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, there is a growing demand for near-surface observing technologies (e.g. geophysical methods) to study agriculturally significant phenomena in the soil (Bitella et al, 2015). Recent studies (Cassiani et al, 2015;Consoli et al, 2017;Satriani et al, 2015) demonstrated that these techniques can improve irrigation operations by providing information regarding the optimal amounts and timing of irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…27, núm. 1, e2712172 Primavera 2021 árboles adquieren y movilizan a lo largo de todo el perfil (Bitella et al, 2015;Jones, Cassidy, Thomas, Plante y Pringle, 2009;Zenone et al, 2008) y que no solo incluye el suelo, sino también el lecho de roca degradada química y físicamente (roca intemperizada), donde la rizosfera se extiende comúnmente (Dawson, Hahm y Crutchfield-Peters, 2020;Rodriguez-Robles, Arredondo, Huber-Sannwald, Ramos-Leal y Yepez, 2017).…”
Section: Aplicaciones Y Profundidad En La Investigación Agrícola Y Forestalunclassified
“…Los desarrollos propuestos por la geofísica han incluido métodos eléctricos y electromagnéticos, como son las tomografías de resistividad eléctrica (ERT, por sus siglas en inglés) y el radar de penetración terrestre (GPR, por sus siglas en inglés), desarrollados para el monitoreo del agua, la evaluación de la salinidad y el mapeo del levantamiento del suelo (Butnor, Doolittle, Kress, Cohen y Johnsen, 2001;Chow y Rees, 1989;Halvorson y Rhoades, 1974;Vanderborght, Huisman, van der Kruk y Vereecken, 2013). En la actualidad, las aplicaciones agrícolas y forestales de los métodos geofísicos de ERT y GPR continúan aumentando rápidamente; además, otros métodos geofísicos, como la magnetometría y sísmica, ahora están comenzando a encontrar igualmente un uso en estas disciplinas (Bitella et al, 2015;Cimpoiasu, Kuras, Pridmore y Mooney, 2020).…”
Section: Introductionunclassified
“…Agriculture 4.0 can be considered the evolution of agriculture 20 years ago. In the first two decades of the 21 st century, the advancement of geomatics technology produced new tools and/or improved existing techniques for nearsurface geophysical surveys (and therefore applicable to agricultural soil) in a robust, cost-effective and non-invasive way (Bitella et al, 2015). This is the case of electromagnetic devices that were extensively used in precision agriculture, alone or in combination with information on the ground, to help delineate uniform management zones.…”
Section: Introductionmentioning
confidence: 99%